Orbital Angular Momentum Divider of Light - Hailong Zhou; Jianji Dong; Jian Wang; Shimao Li; Xinlun Cai; Siyuan Yu; Xinliang Zhang (IEEE Photonics Journal)
Manipulation of orbital angular momentum (OAM) of light is essential in OAM-based optical systems. In particular, the OAM divider, which can convert the incoming OAM mode into one or several new smaller modes in proportion at different spatial paths, is very useful in OAM-based optical networks. However, this useful tool has rarely been reported. Here, we put forward a passive OAM divider based on coordinate transformation. The device consists of a Cartesian to log-polar coordinate converter and an inverse converter. The first converter converts the OAM light into a rectangular-shaped plane light with a transverse phase gradient, and the second converter converts the plane light into multiple diffracted light. The OAM of zeroth-order diffracted light is the product of the input OAM and the scaling parameter. The residual light is the output from other diffracted orders. Furthermore, we extend the scheme to realize equal N-division of OAM and arbitrary division of OAM. The ability of dividing OAM shows huge potential for OAM-based classical and quantum information processing.